Pengaruh Awareness Promosi Kesehatan dan Intensitas Word of Mouth Terhadap Minat Melakukan Vaksinasi Kanker Serviks pada Mahasiswi Bidang Kesehatan - Amelia Devi Prasanti; Sri Widowati Herieningsih (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
This research is motivated by the low interest of female students in vaccination of cervical cancer, whereas the number of patient of this disease is increasing from year to year. Some concerned about this issue do various health promotions. This study aims to determine the effect of awareness of health promotion and word of mouth intensity to the interest of vaccination of cervical cancer in female health students. This research is explanatory research with 80 samples and taken with non probability sampling technique. Data analysis in this research use logistic regression analysis. The results showed that there is a significant influence between awareness of health promotion with interest in vaccinating cervical cancer with a significance value of 0.003 and regression coefficient 0.655. This means that the higher awareness of cervical cancer health promotion, the higher the interest in vaccination of cervical cancer in female health students. In the second hypothesis shows there is a significant influence between the intensity of word of mouth on the interest of vaccinating cervical cancer with a value of 0.000 significance and regression coefficient of 0.580. This means that the higher the intensity of word of mouth then the higher the interest of female students to perform cervical cancer vaccination. Further research is expected to examine more about other factors that may affect the interest in vaccinating such as the effect of endorsers.